Terapia gênica com interferon-alfa no controle do câncer colorretal - Gorgulho, Carolina Mendonça [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Interferon alpha (IFN-α) is a type I IFN with great therapeutic potential, since it is able to directly fight tumor cells and enhance the maturation of dendritic cells (DCs), the main antigen-presenting cells, required for an effective antitumor response. However, the systemic administration of cytokines can induce severe collateral effects. Therefore, the induction of cytokine secretion in situ should represent a more adequate approach for cytokine-based immunotherapy. Thus, the goal of this study was to induce IFN-α secretion by colon cancer cells by transduction with a lentivirus vector carrying the human IFN-α gene, followed by analysis of its immunomodulatory potential over DCs. Transduction was made with different multiplicities of infection (MOIs - 0.3, 1.0, 2.0 and 4.0) to evaluate the dose-dependent effects. Such cells were co-cultured with monocyte-derived DCs from healthy donors (DC-0.3, DC-1.0, DC-2.0 and DC-4.0). Forty-eight hours later, DCs were evaluated for their phenotype (surface activation/maturation markers) by flow cytometry, their ability to induce allogeneic response in a mixed leukocyte reaction (MLR) and effectiveness to induce cytotoxic T cells. We observed that transduction with Lego-GFP, but not Lego-IFN, increased tumor cells' immunogenicity with up-regulation of the markers CD54 and HLA-DR. Co-culture of Lego-IFN-transduced tumor cells with DCs slightly enhanced their activation phenotype but not their potential to stimulate T cell proliferation in vitro. Furthermore, we observed that lymphocytes cultured with DC-2.0 produced higher levels of IFN-γ, suggesting an induction of Th1 profile on T cells, while DC-GFP induced more IL-10 and IL-4. Additionally, DC-4.0 was more efficient in generating cytotoxic T lymphocytes (CTLs) that the control DC, however DC-GFP induced even more CD8+T cell proliferation. The enhancement of tumor cell immunogenicity and the superior induction of CLTs ...

O interferon alfa (IFN-α), um IFN do tipo I, se apresenta como uma citocina com grande potencial terapêutico, pois atua no combate direto às células tumorais, além de agir sobre a maturação de células dendríticas (DCs), que são células apresentadoras de antígenos profissionais e peças chave na elaboração da uma resposta antitumoral. Entretanto, a administração sistêmica de citocinas pode produzir toxicidade importante nos pacientes, de modo que a indução de sua produção in situ poderia representar uma forma de imunomodulação mais adequada. Assim, o objetivo deste estudo é verificar a ação de vetores lentivirais carregando o gene do IFN-α para transdução de células tumorais, permitindo assim a produção localizada de IFN-α, a fim de explorar, in vitro, seu potencial lítico e imunomodulatório sobre DCs. Vetores lentivirais carregando o gene do IFN-α humano (Lego-IFN) ou GFP (Lego-GFP) foram utilizados para a transdução in vitro de células de câncer colorretal. A transdução foi feita com diferentes multiplicidades de infecção (MOIs - 0.3, 1.0, 2.0, 4.0) para avaliarmos o efeito dose-dependente, seguido de co-cultura com DCs derivadas de monócitos de doadores saudáveis (DC-0.3, DC-1.0, DC-2.0, DC-4.0). Após 48h de co-cultura, as DCs foram avaliadas fenotípica e funcionalmente, através da análise dos marcadores de membrana por citometria de fluxo, capacidade de aloestimulação e de indução de linfócitos T citotóxicos (CTLs). Nós observamos que a transdução com Lego-GFP, mas não com Lego-IFN, aumentou a imunogenicidade das células tumorais, com aumento de expressão de CD54 e HLA-DR. A co-cultura de DCs com células tumorais transduzidas com Lego-IFN aumentou discretamente seu perfil de ativação, mas não seu potencial aloestimulatório in vitro. Observamos que linfócitos cultivados com DC-2.0 produziram níveis mais altos de IFN-γ, sugerindo a indução de um perfil Th1, enquanto que...
Keywords: Colon (Anatomia) - Cancer; Reto Câncer; Citocinas; Interferon; Células dendríticas; Colon (Anatomy) - Cancer